SAT-105 The Natural History of Pituitary Cysts in Patients with Growth Hormone Deficiency and Idiopathic Short Stature - El-Naghy, Zeyad (J Endocr Soc, 2020)
Background: The sequential follow-up of simple fluid-filled pituitary cysts (PC) has not been fully elucidated. In this study, we further report our follow up of PCs in a cohort of pediatric patients (PTs). Objective: To further analyze the sequential cyst volume (CV) change in short children. Patients and Methods: A pediatric endocrinology and neuroradiology center was queried for the presence of PCs. PTs who underwent multiple high resolution post-contrast MRIs (1mm slices) were subjects of this study. PTs with additional MRI abnormalities were excluded. Pituitary volumes (PV) and CVs were measured using the ellipsoid formula (LxWxH/2). The percentage of the gland occupied by the cyst (POGO) was measured and calculated. A cyst with a POGO ≤15% was defined as a small pituitary cyst (SPC), and a POGO >15% was defined as a large pituitary cyst (LPC). 34 PTs met inclusion criteria, all of whom were diagnosed with short stature (23 growth hormone deficient (GHD) PTs and 11 idiopathic short stature (ISS) PTs). All PTs were receiving GH during data collection. Results: The mean (MN) and median (MD) ages for these subjects were 10.7 yrs ±3.5 and 11.1 yrs, respectively (RSP). Of the 34 PTs, 24 PTs’ (71%) initial MRI demonstrated a SPC and 10 PTs’ (29%) initial MRI demonstrated a LPC. The MN and MD times between first and second MRIs were 1.23 yrs and 0.83 yrs RSP, with a range (RG) of 0.14 to 4.08 yrs. The MN and MD ΔCV for all PTs was 23.33% ±179.17% and -25.94% RSP, with a RG of -100.00% to 763.94%. The MN and MD ΔPOGO by the cyst for all PTs was 48.59% ±313.26% and -36.84% RSP, with a RG of -100.00% to 1734.79%. The MN and MD ΔCV for PTs with a SPC was 10.68% ±2.65% and 11.09% RSP, with a RG of -100.00% to 763.94%. The MN and MD ΔPOGO by the cyst for PTs with a SPC was 78.33% ±369.96% and -31.34% RSP, with a RG of -100.00% to 1734.79%. The MN and MD ΔCV for PTs with a LPC was -24.60% ±51.89% and -26.57% RSP, with a RG of -88.57% to 91.38%. The MN and MD ΔPOGO by the cyst for PTs with a LPC was -22.79% ±44.90% and -40.46% RSP, with a RG of -80.95% to 47.11%. Statistical analysis showed no significant %ΔCV or %ΔPOGO when comparing male vs. female, SPC vs. LPC, GHD vs. ISS, or pre-pubertal vs. pubertal PTs. Analysis of ΔPOGO of the 24 SPC PTs demonstrated that 4 (17%) of them developed into LPCs. Analysis of the 10 LPC PTs showed that 6 (60%) of them shrunk into SPCs, one of which re-enlarged into a LPC, and another of which fluctuated between LPC and SPC over a period of 7.34 yrs and 9 sequential MRIs. None of the PTs experienced significant sequelae related to their PCs. Conclusion: CV can change greatly over time, however few sequelae should be expected. LPCs tend to demonstrate major changes in size and should be tracked for CV change. A minority of SPCs will develop into LPCs. Prediction of change in CV over time requires more sequential data. Change in CV did not appear to be influenced by GH therapy.